Prenatal exposure to polybrominated diphenyl ethers and inattention/hyperactivity symptoms in mid to late adolescents - Park, Seonyoung; Cowell, Whitney; Margolis, Amy E.; Sjodin, Andreas; Jones, Richard; Rauh, Virginia; Wang, Shuang; Herbstman, Julie B. (Frontiers in Epidemiology, 2023)
Introduction Prenatal exposure to polybrominated diphenyl ethers (PBDEs) has been associated with increased symptoms of attention deficit/hyperactivity disorder (ADHD) in early to middle childhood, as well as early adolescence. However, data are limited for the long-lasting impact of exposure on outcomes assessed across the entire adolescent period and the sex-specificity of such associations. Methods We investigated the association between continuous natural-log-transformed cord plasma PBDE concentrations and ADHD rating scale 4th edition (ADHD-RS-IV) score from mid adolescence (approximately 11 years old) to late adolescence (approximately 17 years old). The study sample includes a subset (n = 219) of the African American and Dominican children enrolled in the Columbia Center for Children's Environmental Health Mothers and Newborns birth cohort. We used generalized estimating equations to account for the repeated measure of ADHD-RS scores. We examined interactions between exposure to PBDE and sex using cross-product terms and sex-stratified models. In addition, we used linear regression using an age-stratified sample as a sensitivity analysis. Results and Discussion Associations between prenatal exposure and parents’ reports of ADHD symptoms varied by sex (p-interaction <0.20), with positive relationships observed among girls but not boys from sex-stratified models. Our finding suggests prenatal exposure to PBDE may affect ADHD symptoms assessed during middle to late adolescence and the sex-specificity of such impact. Our results can be confirmed by future studies with larger and more diverse samples.